Advancements in Nursing Practices: Bridging Evidence-Based Care and Clinical Innovation - Faten Mohammed Alenazi; Saja Mohammed Alsaedi; Aziza Mohammed Alsultan; Wafa Ali Alfareed; Haya Mubarak Saleem Alotaibi; Malak Ramadan Alenizi; Noha Abdullah Bin Rashood; Mazyounah Hassan Aldossarry; Soso Mohammed Rashid Al Masoud; Eman Hamad Bin Ali; Mohammed Salah Albalawi; Abduallah Amer Alenezy (International Journal of Medical Toxicology and Legal Medicine, 2024)
Healthcare has experienced substantial transformations in recent decades to integrate new technology and address the changing demands of individuals and the community. This transition has supplanted conventional approaches such as prescription papers and patient charts with digital displays and software. The implementation of these improvements has positively influenced patient outcomes and increased the number of lives saved. Healthcare, including nursing, is undergoing dramatic changes due to the integration of artificial intelligence (AI) and robotic technologies. Digital technologies exert a significant global impact on nursing, highlighting the necessity for nurses to thrive in both clinical and technology domains. Virtual reality (VR) is a simulation modality that employs sophisticated technology and augmented reality (AR) enhancements. Virtual reality simulations provide nursing students with a significant chance to perform high-risk interventions on virtual patients, enabling them to acquire experience without jeopardizing patient safety.